Penerapan Desain Pembelajaran Role Play dalam Meningkatkan Motivasi Belajar Pendidikan Kewarganegaraan (PKn) di MI NW Pungkang - fahrurrozi (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2020)
The problem examined in this study is the application of the Role Play learning design to increase the learning motivation of fourth grade students of MI NW Pungkang. This study aims to determine the application of the Role Play learning design in increasing the learning motivation of grade IV students at MI NW Pungkang on the Competency Standards for the Village Government System. This research is a Classroom Action Research (CAR) taken in one cycle. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. As for who became the research subjects were grade IV MI NW Pungkang totaling 17 students. Data collection techniques use observation techniques, questionnaires and interviews about the application of role play learning designs. The data analysis techniques used were qualitative and quantitative data analysis. Based on the results of the study it was concluded that the application of the role play learning design could increase the learning motivation of fourth grade students of MI NW Pungkang as evidenced by an increase in the percentage of observation results, the students' learning motivation score was 11.25% from the pre-cycle. 62.63% increased to 82.22% in silu I. In addition, based on the results of the questionnaire data analysis, it can also be concluded that there was an increase in student learning motivation scores by 7.75% from the initial observation score of 62.63% to cycle I of 82.22%. When viewed classically, the remaining learning motivation which is categorized as medium and high also increases from 60.10% to 93.33%. The results of interviews with teachers and students related to the implementation of role play learning designs also received a positive response